Liberty on Parole? Challenges in Interactivity (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
Interactivity permeates AI, virtual reality and augmented reality, affecting sensory-motor experiences and creative processes. However, this pervasiveness comes with constraints, as virtual interfaces simultaneously enhance and restrict user freedom. This leads to philosophical reflections on user emancipation and the interplay between freedom and structural constraints in interactive relationships with digital technologies. The dynamic landscape raises important questions about the development of freedom in a digitally mediated world.
Keywords: Interactivity; Material Engagement; Artificial Intelligence; Imagination; Mixed Realities